2022
DOI: 10.3390/nano12050883
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Chemical Method for Determining the Surface Concentration of Stone–Wales Defects for 1D and 2D Carbon Nanomaterials

Abstract: A quantitative method is proposed to determine Stone–Wales defects for 1D and 2D carbon nanostructures. The technique is based on the diene synthesis reaction (Diels–Alder reaction). The proposed method was used to determine Stone–Wales defects in the few-layer graphene (FLG) nanostructures synthesized by the self-propagating high-temperature synthesis (SHS) process in reduced graphene oxide (rGO) synthesized based on the method of Hammers and in the single-walled carbon nanotubes (SWCNT) TUBAL trademark, Russ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Figure 1 a shows an HRTEM image of the irradiated N-MWCNT side wall having a near-cylindrical bamboo structure with an average outer diameter of ~20 nm. As can be seen, the outer side of the tube reveals a large number of Stone–Wales defects (arrows) compared to the initial N-MWCNT (see Figure S1 ) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 a shows an HRTEM image of the irradiated N-MWCNT side wall having a near-cylindrical bamboo structure with an average outer diameter of ~20 nm. As can be seen, the outer side of the tube reveals a large number of Stone–Wales defects (arrows) compared to the initial N-MWCNT (see Figure S1 ) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…To eliminate the systematic error of the experiment, we specially set up a blank experiment (there was no α-methylstyrene in the solution), which showed the absence of sorption of o-xylene on the surface of the selected series of nanocarbons. The technique is described in detail in [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work [ 21 ], we showed the possibility of synthesizing FLG under self-propagating high-temperature synthesis (SHS) conditions from cyclic biopolymers. An important advantage of FLG synthesized by this method is the absence of Stone–Wales defects [ 22 ], which is almost inevitable in synthesis by other methods. We found that FLG nanostructures synthesized by the SHS method could significantly improve nitrile butadiene rubber’s complex strength and thermos physical properties [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, SW defects are not always artificial imperfections and can be commonly generated during synthesis of CNTs [ 40 , 41 ]. Furthermore, tensile [ 42 , 43 ] and compressive [ 29 ] load application can produce SW defects even in pristine CNTs.…”
Section: Methodsmentioning
confidence: 99%